Relationship of Self-Reported Ability to Weight-Bear Immediately After Injury as Predictor of Stability for Ankle Fractures. (September 2016) - Chien, Bonnie; Hofmann, Kurt; Ghorbanhoseini, Mohammad; Zurakowski, David; Rodriguez, Edward K.; Appleton, Paul; Ellington, J. Kent; Kwon, John Y.
Background: Determining the stability of ankle fractures, particularly Weber B fibula fractures, can be challenging. Ability to weight-bear after injury may be predictive of stability. We sought to determine whether patients' ability to weight-bear immediately after injury was an effective indicator for ankle stability following fracture. Methods: A prospective review was conducted of patients sustaining ankle fractures. Patients' ability to weight-bear after injury was elicited and correlated with ankle radiographs, which were deemed stable or unstable based on commonly used indices to assess stability. Results: For the entire cohort (n = 121), patients who were able to weight-bear immediately after injury were over 8 times more likely to have a stable fracture than those who could not (odds ratio [OR] = 8.6, P < .001). Positive predictive value (PPV) for being able to fully weight-bear as it related to stability was 73%. Inability to weight-bear was 85% specific among patients with an unstable fracture. When analyzing patients with radiographic isolated fibula fractures (n = 67), PPV = 82%, negative predictive value [NPV] = 53%, specificity = 79%, whereas the OR was 5.0 ( P = .003) for those who could weight-bear having a stable fracture. When subanalyzing patients who presented with isolated fibula fractures and anatomic mortises (n = 43), PPV = 74%, NPV = 52%, specificity = 62%, whereas the OR was 3.6 ( P = .07) for those who could weight-bear having a stable fracture. Conclusion: Patients' ability to weight-bear immediately after injury was a specific and prognostic indicator for stability across a range of ankle fracture subtypes. Patients with an isolated fibula fracture and anatomic mortise were 3.6 times more likely to have a stable fracture if they were able to fully weight-bear at the time of injury. Although a patient's history does not preclude the need for appropriate imaging studies and clinical judgment, it may aid in the assessment of ankle stability following fracture. Level of Evidence: Level II, clinical diagnostic.